Force and Deformation Analysis of H(t)-T Loaded Pile Based on Pasternak Foundation Model - JIANG Jie, CHEN Lijun, CHAI Wencheng, AI Yonglin, OU Xiaoduo, GONG Jian (Shanghai Jiaotong Daxue xuebao)
The force and deformation of the pile foundation under the combined action of horizontal dynamic load H(t) and torque T are rather complicated. In order to more accurately analyze the internal force and displacement of the H(t)-T combined loaded piles, the shear effect of soil on the pile side is considered based on the Pasternak foundation model, and the H(t)-T coupling factor is introduced to reveal the influence mechanism of multi-directional load on pile response. Then, the virtual work principle is used to derive the comprehensive stiffness matrix of the pile element, and the modified finite beam element method is used to obtain the numerical solution of the internal force and displacement of the H(t)-T combined loaded piles. The results are compared with the results of the existing theoretical solutions and finite element simulation. The parametric analysis shows that soil shear effect can restrain the horizontal displacement of the pile, but has less effect on torsional deformation. The horizontal dynamic load enhances the torsional bearing capacity of the pile, and the torsional angle of the pile top is reduced by 22.6% when the horizontal dynamic load amplitude increases from 0.2Qu to 1.0Qu. Increasing the dimensionless frequency of the dynamic load will reduce the displacement of pile top and the maximum bending moment of pile body. The dynamic effect of simple harmonic load will be weakened with the increase of pile burial depth. The beam element model significantly reduces the number of discrete units and computation time, which can effectively improve the computational efficiency.